Exploring The Lived Experiences of Grade 6 Struggling Readers in Elementary Schools in Quezon City - Bautista, Maria Daphny; Buhain, Vivian; Del Rosario, Ligaya; Barrientos, Ma. Ofelia; Cainglet, Ronnie; Tabunda, Dorislyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of Grade 6 struggling readers in selected elementary schools in Quezon City to understand the academic, emotional, social, and environmental factors influencing their reading difficulties and identify evidence that could strengthen literacy interventions. Guided by a transcendental-phenomenological approach, the study employed a qualitative research design involving six purposively selected Grade 6 learners with identified reading difficulties. Data were collected through researcher-developed semi-structured interviews, supported by document analysis and arts-based activities, and analyzed using Moustakas' transcendental phenomenological method with triangulation to enhance credibility. The findings revealed that participants experienced greater difficulty reading English than Filipino because of limited vocabulary, weak pronunciation, poor comprehension, and low reading fluency. These challenges negatively affected their emotions, motivation, classroom participation, academic performance, and self-esteem. Contributing factors included limited family and teacher support, inadequate reading materials, inconsistent reading practice, environmental distractions, excessive gadget use, and peer bullying. Despite these challenges, encouragement from parents, teachers, and peers promoted resilience, improved confidence, and strengthened learners' motivation to continue developing their reading skills. The study concludes that reading difficulties are shaped by interconnected academic, emotional, social, and environmental factors and require collaborative support from families, schools, and communities. It recommends strengthening home-school partnerships, implementing differentiated and phonics-based reading instruction, providing accessible literacy resources, fostering supportive classroom environments, and conducting further research on reading intervention programs. The study supports Sustainable Development Goal (SDG) 4: Quality Education, SDG 10: Reduced Inequalities, and SDG 17: Partnerships for the Goals by promoting equitable literacy development, inclusive educational opportunities, and collaboration among educational stakeholders. Its findings contribute to educational and community sustainability by informing evidence-based literacy interventions, strengthening stakeholder partnerships, and supporting policies that improve learning outcomes and educational equity for struggling readers.
Keywords: Academic Performance; Grade 6 Struggling Readers; Literacy Development; Qualitative Research; Quezon City; Reading Difficulties; Reading Interventions; Transcendental Phenomenology